2020
DOI: 10.26633/rpsp.2020.54
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and newborn health: systematic review

Abstract: Objective. To describe perinatal and neonatal outcomes in newborns exposed to SARS-CoV-2. Methods. A systematic review was conducted by searching PubMed Central, LILACS, and Google Scholar using the keywords ‘covid ’ AND ‘newborn’ OR ‘child’ OR ‘infant,’ on 18 March 2020, and again on 17 April 2020. One researcher conducted the search and extracted data on demographics, maternal outcomes, diagnostic tests, imaging, and neonatal outcomes. Results. Of 256 publications identified, 20 met inclusion criteria and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
34

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 26 publications
4
67
0
34
Order By: Relevance
“…In their Practice Advisory on the Novel Coronavirus 2019 (SARS-CoV-2), the American College of Obstetricians and Gynecologists (ACOG), state that infants born to mothers with confirmed COVID-19, should be considered persons under investigation (PUI), and as such should be isolated according to the Infection Prevention and Control Guidance for PUIs [54,55]. They further [18,38,40,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…In their Practice Advisory on the Novel Coronavirus 2019 (SARS-CoV-2), the American College of Obstetricians and Gynecologists (ACOG), state that infants born to mothers with confirmed COVID-19, should be considered persons under investigation (PUI), and as such should be isolated according to the Infection Prevention and Control Guidance for PUIs [54,55]. They further [18,38,40,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from China [3,9] and the United States of America [10] showed that a majority of pregnant women that were positive for COVID-19 delivered via caesarean section because of foetal distress [11]. There is limited evidence concerning the possible maternal-foetal transmission and neonatal infection, and case reports have described COVID-19 in healthy newborns as a mild self-limiting disease [3,4,12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to adults, children seem to be less affected by SARS-CoV-2 infection as they are usually asymptomatic or have mild symptoms [ [1] , [2] , [3] , [4] ]. However, little is known about disease severity in neonates, the need for treatment and their role in transmission of SARS-CoV-2 [ 5 ]. It is reported that children or neonates can have high viral loads, while remaining asymptomatic or having mild symptoms [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%